Control of magnetically levitated rotors using stabilizing effects of gyroscopes. (1st March 2022) - Hutterer, Markus; Wimmer, Dominik; Schrödl, Manfred
Abstract: Stable control of magnetically levitated rotors with a high gyroscopic effect is an important subject in the field of rotating machinery. This paper describes a method to address this problem using a cross-coupled control approach. In the low and middle speed range a constant diagonal controller and a speed dependent cross-coupled controller is used. In the high speed range the controller takes advantage of the stabilizing effect of gyroscopes. Hence, no positive diagonal stiffness is required in the high speed range in the tilting control path. The damping of the nutation and precession mode is provided only by the cross-coupled control paths. Thus, no diagonal controller is required for the stabilization of the tilting modes. This circumstance reduces the gain and the bandwidth of the control structure, and therefore decreases the impact of sensor noise and the possibility of destabilizing high frequency flexible modes. In this study the stabilizing effect of magnetically stabilized gyroscopes is derived analytically. Furthermore, the damping effects of the cross-coupled controllers are explained, using the eigenvalues of a simplified system. Simulation results show the output sensitivity of the control structures. Based on this knowledge, the optimal switching point between the control structures can be derived. Finally, experimental results on a turbo-molecular pump validate the effectiveness of the proposed control method. Highlights: Usage of stabilizing effects of gyroscopes for the controller design. Stability analysis of cross coupled control structures. Reduction of the required bandwidth. The performance was significantly increased for high rotor speeds.